Pendekatan Kuantitatif dalam Memahami Dampak Konten TikTok pada Brand Image: Studi Kasus Skintific - Viona, Viona; Rusdi, Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Skintific introduces its brand identity through various social media platforms, especially TikTok. This study aims to assess whether TikTok content affects Skintific's brand image in public opinion. Quantitative methods were used in this study by distributing questionnaires to 100 respondents, who were selected using the Slovin Formula and a purposive or judgmental sampling approach. The theoretical basis underlying this study involves the concept of social media content and brand image. The data processing and analysis techniques involve normality tests, partial tests (t-tests), simple linear regression tests, validity tests, reliability tests, linearity tests, and heteroscedasticity tests. The social media content variable (X) shows a positive regression coefficient with a b value = 0.377 as shown in the regression test results. This indicates that a one-point increase in variable X will result in an increase in brand image (Y) by 0.377. Therefore, the results of the analysis indicate a positive relationship between social media content and brand image. Social media content produced by Skintific on the TikTok platform acts as a significant source of product information for consumers. This influence plays a crucial role in forming a brand image which will later show the benefits of a brand image that has been successfully built and shown to the public. Skintific memperkenalkan identitas mereknya melalui berbagai platform media sosial, terutama TikTok. Penelitian ini bertujuan untuk menilai apakah konten TikTok mempengaruhi citra brand Skintific di opini publik. Metode kuantitatif digunakan dalam penelitian ini dengan cara mendistribusikan kuesioner kepada 100 responden, dan pendekatan pengambilan sampel purposive atau judgmental. Landasan teori yang mendasari penelitian ini melibatkan konsep konten media sosial dan citra merek. Adapun teknik pengolahan dan analisis data melibatkan uji normalitas, uji parsial (uji t), uji regresi linear sederhana, uji validitas, uji reliabilitas, uji linearitas, dan uji heterokedastisitas. Variabel konten media sosial (X) menunjukkan koefisien regresi positif dengan nilai b = 0,377 yang ditunjukkan dalam hasil uji regresi. Hal ini mengindikasikan bahwa kenaikan satu poin pada variabel X akan mengakibatkan peningkatan citra merek (Y) sebesar 0,377. Oleh karena itu, hasil analisis menunjukkan adanya hubungan positif antara konten media sosial dan citra merek. Konten media sosial yang diproduksi oleh Skintific di platform TikTok berperan sebagai sumber informasi produk yang signifikan bagi konsumen.